Biotransformation of trace organic chemicals in the presence of highly refractory dissolved organic carbon. (January 2019) - Hellauer, Karin; Martínez Mayerlen, Sara; Drewes, Jörg E.; Hübner, Uwe
Abstract: Previous studies demonstrated that the transformation of trace organic chemicals (TOrCs) in managed aquifer recharge (MAR) systems is favored under carbon-limited and oxic redox conditions especially, if the dissolved organic carbon (DOC) serving as primary substrate has a refractory character. Since co-metabolism is suggested to be the dominant removal mechanism, it is hypothesized that TOrCs transformation is controlled by the concentration of the refractory carbon under oxic redox conditions. A laboratory-scale soil column experiment mimicking MAR was established to investigate the influence of two different concentrations of highly refractory carbon sources on TOrCs transformation, namely drinking water (DW) and drinking water augmented with humic acid (DW + HA). Oxic redox conditions and carbon-limitation were present in both systems (ΔDOCDW+HA ≈ 0.6–0.7 mg/L; ΔDOCDW ≈ 0.1 mg/L). Of the 12 TOrCs investigated seven exhibited moderate to efficient transformation in both systems with only one compound (diclofenac) showing significantly enhanced (co-metabolic) biotransformation by adding humic acids as primary growth substrate. It is postulated that transformation of some TOrCs is characterized by metabolic degradation under starving conditions (ΔDOC ≤ 0.1 mg/L). By comparing the transformation efficiency of selected TOrCs with previous studies operated under carbon-limited and oxic conditions, an inconsistent behavior of some compounds was observed. These results demonstrate that key factors triggering the transformation of TOrCs are still poorly understood and thus, further investigations regarding the biodegradation pathways of TOrCs, upregulation of key enzymes by the microbial community but also more detailed analysis of the composition of the biodegradable DOC are needed. Highlights: Trace organic chemical (TOrC) transformation during managed aquifer recharge. Establishment of carbon-limited and oxic conditions. Primary substrate: drinking water (DW) and DW augmented with humic acids (HA). No benefit of adding HA as refractory carbon source for co-metabolic transformation. Inconsistent behavior of some TOrCs even under carbon-limited and oxic conditions.